Acoustic emissions and electric signal recordings, when cement mortar beams are subjected to three-point bending under various loading protocols - A. Kyriazopoulos (Fracture and Structural Integrity)
Two experimental techniques are used study the response of cement mortar beams subjected to three-point bending under various load¬ing protocols. The techniques used are the detection of weak electric current emissions known as Pressure Stimulated Currents and the Acoustic Emissions (in particular, the cumulative AE energy and the b-value analysis). Patterns are detected that can be used to predict upcoming fracture, regard¬less of the adopted loading protocol in each experiment. The expe¬rimental results of the AE and PSC techniques lead to the conclusion that when the calculated Ib values decrease, the PSC starts increasing strongly.